Efficacy of Secukinumab in Psoriasis: Post Hoc Gender-Wise Analysis of the SUPREME Study - Stingeni L; Malara G; Conti A; Di Costanzo L; Carrera CG; Burlando M; Malagoli P; Musumeci ML; Bardazzi F; Brazzelli V; Amerio P; De Simone C; et al. (Dove Medical Press, 2023)
Luca Stingeni,1 Giovanna Malara,2,3 Andrea Conti,4 Luisa Di Costanzo,5 Carlo Giovanni Carrera,6 Martina Burlando,7 Piergiorgio Malagoli,8 Maria Letizia Musumeci,9 Federico Bardazzi,10 Valeria Brazzelli,11 Paolo Amerio,12 Clara De Simone,13,14 Sara Trevisini,15 Anna Balato,16 Matteo Megna,17 Francesco Loconsole,18 Catia De Felice,19 Marta Bartezaghi,20 Alice Rausa,20 Elisabetta Aloisi,20 Roberto Orsenigo,20 Antonio Costanzo21,22 On behalf of the SUPREME Study Group1Dermatology Section, Medical and Surgical Department, University of Perugia, Perugia, Italy; 2Dermatology Unit, Hospital "Bianchi Melacrino Morelli", Reggio Calabria, Italy; 3Department of Dermatology, Papardo Hospital, Messina, Italy; 4Dermatologic Unit, Department of Surgery, Infermi Hospital, AUSL Romagna, Rimini, Italy; 5Department of Dermatology, "Gaetano Rummo" Hospital, Benevento UOC Dermatologia, AO G. Rummo, Benevento, Italy; 6U.O. Dermatologia, Fondazione IRCCS Ca' Granda - Ospedale Maggiore Policlinico, Milano, Italy; 7IRCCS San Martino Polyclinic Hospital, Di.S.Sal. Section of Dermatology, Genoa, Italy; 8Dermatology Unit IRCCS Policlinico San Donato, Milan, Italy; 9Dermatology Clinic, University of Catania, Catania, Italy; 10Division of Dermatology, University Hospital Policlinico "S. Orsola-Malpighi", Bologna, Italy; 11Institute of Dermatology, Foundation IRCCS Policlinico San Matteo and University of Pavia, Pavia, Italy; 12Dermatologic Clinic, G. D'Annunzio University, Chieti, Italy; 13Istituto di Dermatologia, Università Cattolica del Sacro Cuore, Rome, Italy; 14Fondazione Policlinico Universitario A. Gemelli - IRCCS, Rome, Italy; 15Dermatology Department, University of Trieste, Trieste, Italy; 16Dermatology Unit, University of Campania "Luigi Vanvitelli", Naples, Italy; 17Section of Dermatology, Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, Italy; 18Department of Biomedical Sciences and Human Oncology, University of Bari, Bari, Italy; 19Department of Clinical Dermatology, Centre for the Study and Treatment of Psoriasis, San Gallicano Dermatological Institute, IRCCS, Rome, Italy; 20Novartis Farma SpA, Origgio, Italy; 21Unit of Dermatology, IRCCS Humanitas Research Hospital, Milan, Italy; 22Department of Biomedical Sciences, Humanitas University, Milan, ItalyCorrespondence: Luca Stingeni, Dermatology Section, Medical and Surgical Department, University of Perugia, Perugia, Italy, Tel +39075-5783881, Email luca.stingeni@unipg.itPurpose: Psoriasis, a common systemic inflammatory disorder, presents with gender-related differences in the quality of life (QoL) and treatment outcomes. This post hoc analysis from the Phase 3b SUPREME study explored gender-related differences in patient characteristics and efficacy of secukinumab 300 mg on Psoriasis Area and Severity Index (PASI) 75/90/100 and impact on QoL using the Dermatology Life Quality Index (DLQI) in patients with moderate to severe psoriasis through week 24.Patients and Methods: The proportion of patients achieving PASI 75/90/100 was computed using a nonresponder imputation approach. Differences between cohorts were analyzed using a logistic regression model. The mean change from baseline in DLQI was computed using the Wilcoxon test.Results: Among the 433 patients (males: 71.6%), females had a higher DLQI than males at baseline (13.1 vs 9.5; P< 0.0001). Males had a slightly higher response for PASI 90 than females at week 16 (80.7% vs 78.1%; P=0.0779) and 24 (83.2% vs 79.7%; P=0.0319). No differences were observed between genders in PASI 100/75 responses at week 24. Both genders showed an improvement in DLQI with secukinumab at week 24 (− 10.9 vs − 8.1, respectively, in females vs males; P=0.0004).Conclusion: In summary, secukinumab was effective in the treatment of psoriasis, irrespective of gender.Keywords: plaque psoriasis, PASI, patient-reported outcomes, Dermatology Quality of Life Index, Hospital Anxiety and Depression Scale